Bitterness quantification and simulated taste mechanism of theasinensin A from tea - Zhang, Jian-yong; Cui, Hong-chun; Feng, Zhi-hui; Wang, Wei-wei; Zhao, Yun; Deng, Yu-liang; Jiang, He-yuan; Yin, Jun-feng; Engelhardt, Ulrich H. (Frontiers in Nutrition, 2023)
Theasinensin A is an important quality chemical component in tea, but its taste characteristics and the related mechanism are still unclear. The bitterness quantification and simulated taste mechanism of theasinensin A were researched. The results showed that theasinensin A was significantly correlated with bitterness of tea. The bitterness threshold of theasinensin A was identified as 65 μmol/L for the first time. The dose-over-threshold (DOT) value of theasinensin A was significantly higher than that of caffeine in black tea soup. The concentration-bitterness curve and time-intensity curve of theasinensin A were constructed. Bitterness contribution of theasinensin A in black tea was higher than oolong and green tea. Theasinensin A had the highest affinity with bitterness receptor protein TAS2R16, which was compared to TAS2R13, TAS2R14. Theasinensin A was mainly bound to a half open cavity at the N-terminal of TAS2R13, TAS2R14, TAS2R16. The different binding capacity, hydrogen bond and hydrophobic accumulation effect of theasinensin A and bitterness receptor proteins might be the reason why theasinensin A presented different bitterness senses in human orah.